Building Relational Understanding Through Hypothetical Learning Trajectory of Probability - Rahmi, Fathur; Sampoerno, Pinta Deniyanti (International Journal of Elementary Education, 2021)
Many researchers found that students have difficulties in understanding probability. Students mostly focus on applying formula to find the solution of problem without knowing what the concept is and why the formula works. It is important for the students to build relational understanding.This underlies the researcher to designÂ  learning of probability as hypothetical learning trajectory. Realistic Mathematics Education (RME) underlies the design of context andactivitiesto be do.This study uses a design research method which consists of three phases isÂ  preparation and design, teaching experiment and retrospective analysis. The data collection technique is done by video recorder, documentation and test questions. The results of the research carried out obtained that student experienced an increase and the gave a good response to in solving the questions.